Is There a Link Between Corporate Rebranding Motives and Strategies? Evidence from the Warsaw Stock Exchange - Natalia K. WOJCIECHOWSKA (Communications of International Proceedings, 2020)
Purpose: This study examines the relationship between the motives and corporate rebranding strategies. Such link was proved on Western markets. Methodology: The research was carried out on the sample of 121 joint-stock companies listed on WSE Main Market and New Connect in Poland. The chi-square test of independence was carried out for each combination of motives and strategies. Findings: Statistical significance was proved for six pairs: micro- and macroeconomic factors and brand name shortening, acquisition and complete brand name change, merger and co-branding, acquisition and brand name shortening, strategic factors and co-branding, strategic factors and brand name shortening. The strongest effect was shown by Cramer’s V for micro- and macroeconomic factors and brand name shortening.  Research & Limitations/Implications: The results confirm that there is a link between motives and corporate rebranding strategies. Further research is required in terms of specific types of mergers and acquisitions and their relations with rebranding strategies. Originality/value: The research makes a notable input in terms of conceptual framework and systematization of definitions as well as new classifications of both rebranding motives and strategies. Empirical study investigates the relationship between corporate rebranding motives and strategies on the Polish market.
Keywords: Competitive Strategy; Motive; Corporate Rebranding; Joint-Stock Company.